Evaluation on Long-Term Test–Retest Reliability of the Short-Form Childhood Trauma Questionnaire in Patients with Schizophrenia - Xiang Z; Liu Z; Cao H; Wu Z; Long Y (Psychology Research and Behavior Management, 2021)
Zhibiao Xiang1 12 23 3, Zhening Liu1 12 23 3, Hengyi Cao4 45 5, Zhipeng Wu1 12 23 3, Yicheng Long1 12 23 3 1Department of Psychiatry, The Second Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of China; 2Mental Health Institute of Central South University, Changsha, Hunan, People’s Republic of China; 3China National Clinical Research Center on Mental Disorders, Changsha, Hunan, People’s Republic of China; 4Center for Psychiatric Neuroscience, Feinstein Institute for Medical Research, Hempstead, NY, USA; 5Division of Psychiatry Research, Zucker Hillside Hospital, Glen Oaks, NY, USACorrespondence: Yicheng Long Email yichenglong@csu.edu.cnBackground: Many studies have reported an association between childhood trauma exposure and schizophrenia. Among these studies, the Short-form Childhood Trauma Questionnaire (CTQ-SF) is one of the most widely used measures of childhood trauma. However, little is known regarding the long-term reliability of the CTQ-SF, especially in patients with psychopathology.Methods: The CTQ-SF was administered to 50 patients diagnosed with schizophrenia from a hospital in Changsha, Hunan, China. These patients were asked to re-complete the CTQ-SF when they were re-hospitalized or received outpatient treatments in the same hospital within 4 years of follow-up. Intraclass correlation coefficient (ICC) was used to assess test–retest reliability of the CTQ-SF over the intervals. Associations of the CTQ-SF with the Positive and Negative Syndrome Scale (PANSS) and Wechsler Adult Intelligence Scale (WAIS) were tested using Spearman correlation coefficients.Results: Among the participants, 35 (70.0%) patients re-completed the CTQ-SF after an interval averaging 11.26 months. Excellent test–retest reliabilities (with ICC > 0.75) were found for the total CTQ-SF score (ICC = 0.772) as well as scores of the emotional abuse (ICC = 0.808), physical abuse (ICC = 0.756), sexual abuse (ICC = 0.877) and physical neglect (ICC = 0.751) subscales. Meanwhile, a moderate test–retest reliability was found for the emotional neglect subscale (ICC = 0.538). At both baseline and follow-up, no significant correlations (p > 0.05) were found between CTQ-SF scores and any other clinical assessments.Conclusion: Our results suggest that CTQ-SF is reliable to assess childhood trauma exposures in schizophrenia over relatively long intervals, regardless of patients’ current symptoms and states of cognition.Keywords: childhood trauma questionnaire, childhood adversity, childhood trauma, schizophrenia, test–retest reliability